Legal Transendence Theory: Traces and Efforts to Build Transendent Legal Paradigm - Zahwa Nabila Putri Maharani; Satrio Ulil Alab; Zella Arina Salsabila; Tyara Dhalih Alfia; Aji Saptaji; Satria Dwi Andyka (Proceeding International Conference Restructuring and Transforming Law, 2022)
George R. Terry suggested that the basic concept of management is divided into 4 phases, namely Planning, Organizing, Actuating and Controlling which are patterns in compiling, processing, and managing an organization to be more organized in achieving its vision and mission. This article will examine the controlling stage as the last series that aims to improve and avoid deviations in employee performance in an organization or agency, also to ensure that every task in the organization and work can be properly maintained to achieve organizational goals. The Inspectorate General of the Ministry of Education and Culture is the Government Internal Supervision Apparatus (APIP) responsible for carrying out internal supervision within the Ministry of Education and Culture to control the operational stage so that it is expected to create effectiveness and efficiency in performance as well as an effort to prevent irregularities by employees. Articles 195 and 196 of Permendikbud No. 45 of 2019 concerning Organization and Work of the Ministry of Education and Culture has mentioned the duties and functions of the Inspectorate General of the Ministry of Education and Culture so as to provide clarity on its authorities and responsibilities which focuses on the formulation and implementation of policies on performance and finance within the Ministry of Education and Culture. The Inspectorate General of the Ministry of Education and Culture divides the duties and responsibilities assigned to members according to their respective skills and abilities. The Inspectorate General of the Ministry of Education and Culture divides the roles in two major units in its organizational structure in order to be able to support the implementation of various planned programs. However, in practice the Inspectorate General of the Ministry of Education and Culture cannot be separated from obstacles when carrying out supervision programs so that often the policies made by the Ministry of Education and Culture are not fully realized against their targets.